2020
DOI: 10.3390/ijms21249765
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Scaffold/Dental Pulp Stem Cell (DPSC) Tissue Engineering Constructs for Bone Defect Treatment: An Animal Studies Literature Review

Abstract: Background: Recently a greater interest in tissue engineering for the treatment of large bone defect has been reported. The aim of the present systematic review and meta-analysis was to investigate the effectiveness of dental pulp stem cells and synthetic block complexes for bone defect treatment in preclinical in vivo articles. Methods: The electronic database and manual search was conducted on Pubmed, Scopus, and EMBASE. The papers identified were submitted for risk-of-bias assessment and classified accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 95 publications
(247 reference statements)
1
26
0
Order By: Relevance
“…Similar to DPSCs, SHED derive from dental pulp. However, due to the developmental differences between deciduous and permanent teeth, SHED express higher levels of genes related to stemness (OCT4, SOX2, NANOG, and REX-1) compared to DPSCs, retaining a higher plasticity through passaging in vitro [ 45 , 46 ]. SHED are highly proliferative and capable of differentiating into a variety of cell types, such as neural cells, osteoblasts, chondrocytes, and adipocytes [ 13 ].…”
Section: Oral Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to DPSCs, SHED derive from dental pulp. However, due to the developmental differences between deciduous and permanent teeth, SHED express higher levels of genes related to stemness (OCT4, SOX2, NANOG, and REX-1) compared to DPSCs, retaining a higher plasticity through passaging in vitro [ 45 , 46 ]. SHED are highly proliferative and capable of differentiating into a variety of cell types, such as neural cells, osteoblasts, chondrocytes, and adipocytes [ 13 ].…”
Section: Oral Mscsmentioning
confidence: 99%
“…The potential of DPSCs for periodontal regeneration may be questionable because of their limited capacity to form cementum [43,44]. A recent revision of the literature reported that DPSCs on synthetic scaffolds are useful to treat bone defects, showing encouraging results of early new bone formation in preclinical animal studies [45].…”
Section: Dental Pulp Stem Cells (Dpscs)mentioning
confidence: 99%
“…In vivo tissue formation ability comparison among MFSCs Bone JBMSCs [197]>DFSCs [152], SCAP [131], SHED [163,170]>DPSCs [107,109], PDLSCs [3,69,77] 5 Stem Cells International cocultured with B cells, they inhibited the production of IgG, IgM, and IgA and suppressed the proliferation of B cells by increasing the expression of PD1 and PD-L1 [69]. HPDLSCs also mediate the macrophage polarization.…”
Section: Tissuementioning
confidence: 99%
“…Among MSCs discovered up until now, DPSCs have showed high mitochondrial respiratory ability, which is an indicator of the initiation of the differentiation to odontoblasts and osteoblast [ 108 ]. Accompanied with a synthetic scaffold, DPSCs have successfully increased new bone formation in rats, rabbits, sheep, and swine animal models [ 109 ]. Moreover, Wang et al have invented the DPSC rejection medicine to regenerate alveolar bone and it has recently been placed in phase II clinical trials [cde.org.cn identifier: CXSL1700137 ].…”
Section: Dental Pulp Stem Cellsmentioning
confidence: 99%
“…Indeed, functional CB 1 receptors have also been reported in human odontoblasts [ 96 ]. Cannabinoid treatment of rat odontoblasts has been shown to promote the formation of “reparative dentin” by modulating extracellular Ca 2+ entry [ 97 ], which might be the mechanism for CB 1 -mediated dental pulp tissue repair via the matrix metalloproteinase–2 activation in dental pulp cells [ 98 , 99 , 100 , 101 , 102 ].…”
Section: Introductionmentioning
confidence: 99%